Multi-Satellite Cooperative Beamforming ALOHA for LEO Satellite IoT Networks - Liu, Rui; Hong, Tao; Ding, Xiaojin; Wang, Yunfeng; Zhang, Gengxin (Frontiers in Space Technologies, 2021)
In this paper, we proposed a cooperative beamforming ALOHA (CBA) scheme based on linearly constrained minimum variance (LCMV) criterion for low earth orbit satellite (LEO) IoT networks to solve the problem of ‘deadlock’ in multi-satellite scenario. In LEO multi-satellite common-view area, packets can be received by multiple satellite receivers by sending them only once, which forms the concept of spatial diversity. The cooperative beamforming collision resolution technique combined with successive interference cancellation (SIC) scheme is design to efficiently resolve packet collision by iteration way at the gateway station. The performance of CBA scheme is evaluated via mathematical analysis and simulations. Simulation results show that the proposed CBA scheme can effectively solve the problem of ‘deadlock’ and improve the performances of random access (RA) compared with benchmark problems.